Transnational Ideologies and Religious Local Wisdom - Machasin MM (Center for Research and Development of Religious Literature and Heritage, 2017)
This paper Is about the dynamic of discourse between the so called Transnational ideologies and Religious local wisdom. The reason this discourse is necessary to understand well in relation to religious life in Indonesia is because some transnational ideologies have succeeded in attracting the attention of some Islamic people. This is a paper with an anthropological approach. Thus, the description is based on phenomenological observation. This paper will look at some transnational ideologies offerings that attracted some Islamic historical experiences which had built the grandour of Islamic civilization as the nostalgia to back up their offer. One of the example is the idea of Khilafah which is propagated by the so called Hizbut Tahrir. Another is the Jihad movement which is propagated by for instance ISIS and previously al Qaida. This paper will analyze the reasons why some Islamic people are very interested in these movements while what transnational ideologies offer is actually the solidarity to be Muslims based on the bad situation of the Middle East. However, these transnational movements have gain their supporters in the name of Islamic solidarity based on the historical example of Islamic golden age. Therefore, the ideas offered is constructing new Islamic world order based on Islamic teachings and form in accord with their framework and paradigm. The New Islamic World order will leash the suffer of Islamic people from unjust treatment the so called western domination. In relation to this in Indonesian case, it is important to consider religious local wisdom as a filter to this propagation. It is because religious local wisdom will give deeper understanding to the people how to understand the teaching of their religion based on the context of their life and their local religious heritage without deviating from the essence of religion.